Producer group participation in the trade adjustment assistance program for farmers before and after the American Recovery and Reinvestment Act of 2009. (July 2019) - Lee, Yu Na; Chau, Nancy; Just, David R.
Highlights: TAAF program participation has more than doubled after the ARRA. It is uncertain whether the ARRA has caused the increase in program participation. Commodity characteristics matter the most in TAAF program participation. Pre-ARRA, incentives to mitigate price risk drove TAAF program participation. Post-ARRA, there is a substantial change in the TAAF's role. Abstract: The Trade Adjustment Assistance for Farmers (TAAF) program was established in 2002 to help farmers adversely affected by surges in imports. The program has been underused by farmers and, as a result, the American Recovery and Reinvestment Act (ARRA) of 2009 redesigned the program by loosening the eligibility criteria and changing the structure of the cash assistance. This study examines the factors that incentivize producer groups to file petitions for the TAAF program and whether there exists a cross-program relationship between the TAAF and non-TAAF farm safety net programs in periods before and after the ARRA revisions. We find that, after the ARRA, participation in the program has more than doubled, but it is uncertain whether this increase in participation is a direct consequence of the ARRA revisions. In fact, results indicate that time-invariant characteristics of commodity groups are the most important factors of TAAF participation. We also find some evidence that incentives to mitigate negative price risk drove petitioning activities for the TAAF program before the ARRA. This is further confirmed by a cross-program analysis in which TAAF petitions increase when cash receipts decrease from the non-TAAF farm safety net programs that offer risk management schemes similar to that of the TAAF. After the ARRA, such a cross-program relationship is no longer observed. Indeed, the TAAF program after the ARRA subsidized producer training and business planning in response to import competition rather than simply providing a form of price insurance. This new focus might have substantially changed the drivers of participation.